Development of Electronic Modules in Education to Understanding through Physical Activity - Pondi Ahmad Ariski; Asep Sujana Wahyuri; Khairuddin Khairuddin; Ahmad Chaeroni (Jurnal Penelitian Pendidikan IPA, 2024)
This study aims to develop an E-Module for Physical Education (PE) learning, focusing on table tennis for seventh-grade students. The development model used is a modification of the Borg and Gall model, consisting of ten stages: potential and problem identification, data collection, product design, design validation, design revision, product trial, product revision, usage trial, usage revision, and mass production. The E-Module integrates various multimedia elements such as text, images, videos, animations, and audio to enhance student engagement. The validation results showed that the E-Module was highly valid, with scores of 92% for content experts, 95% for media experts, and 91% for language experts. The practicality test indicated that the E-Module was highly practical for use, with a score of 90%. The effectiveness test, based on small-scale and large-scale trials, showed scores of 82.5% and 90%, respectively, indicating that the E-Module was very effective in improving students' understanding of table tennis techniques and strategies. In conclusion, the E-Module proves to be an effective, flexible, and accessible learning tool that supports the implementation of the Kurikulum Merdeka in PE learning, particularly in table tennis